(untitled) (FULafia Journal of Science and Technology, 2026)
Carbapenem is a class of antimicrobial agent reserved for infections cause by multidrug-resistant microorganisms. This review, using a public health focused approach, aimed to understand and describe the current status of CR in Nigeria in relation to common causes of infections and drugs recommended in WHO treatment guidelines. Assessment of the prevalence of Carbapenemase-resistance Gram-negative bacteria is necessary in Nigeria. This article reviewed the previously published literature on the Prevalence of Carbapenemase-resistance Gram-negative bacteria. There were 100 % isolation of Gram-negative bacteria such as Escherichia coli, Klebsiella spp., Pseudomonas aeroginosa, Shigella spp., Salmonella spp. Citrobacter spp., Proteus spp., Serratia spp., Enterobacter spp., Morganella morganii, Providenciae spp. and Acinetobacter baumanii in all the studies reviewed. Veronna integrin-encoded, New Delhi methallo, New Delhi methallo-1, New Delhi methallo-5, Klebsiella pneumoniae Carbapenemase, Guiana extended-spectrum beta-lactamase, Oxacillinases-48, Oxacillinases-181, Dhahran Hospital in Saudi Arabia b-lactamase were some of resistance mediated genes observed in some of studies in Nigeria. Exhaustive search for recent articles (2011–2024) was conducted using PubMed, Google search engine, AJOL and other relevant databases in accordance with the PRISMA guidelines. Article retrieval and screening were done using a structured search string and strict inclusion/exclusion criteria. Carbapenem-resistant in Gram-negative bacteria is a clear and present danger in Nigeria, which needs strong surveillance to curb this menace. Public health departments must monitor carbapenem resistant isolates.